PENGEMBANGAN PENDIDIKAN KARAKTER DALAM PENDIDIKAN JASMANI DAN OLAHRAGAPADA PENDIDIKAN ANAK USIA DINI - Hariadi, Hariadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2015)
Abstract: Character education is an efforts that is designed and implemented systematically to embedded the values ​​of learner behaviour associated with the God, ourselves, human beings, the environment, and nationality embodied in thoughts, attitudes, feelings, speaking , and actions based on religious norms, laws, manners, culture, and customs. Physical Education and Sport (PENJASOR) is essentially a Education processes that utilizes physical activity (motion) to produced a holistic change in individual quality, like on physical, mental, and emotional. Physical education treated the children as a unified whole, total creature, rather than just think of it as someone who separated physical quality and mental. Through the Penjasor learning process is a medium that is considered very precise and powerful in Established of a system of values ​​and character. That aka materialized when given stimulus as early as possible in accordance with the laws of child development.